A novel incision design for Vibrant SoundBridge®︎ implantation prior to auricular reconstruction for microtia - Naohiro Ueda; Takatoshi Yotsuyanagi; Ken Yamashita; Hidekane Yoshimura; Yutaka Takumi; Masahiro Takahashi; Satoshi Iwasaki; Shunsuke Yuzuriha; Shin-ichi Usami (PLoS ONE, 2025)
Objective This study aimed to present and evaluate a surgical approach for placing a Vibrant Soundbridge® (VSB) device prior to auricular reconstruction in patients with microtia atresia. The goal was to determine whether an incision line for VSB implantation, located sufficiently posterior to the planned area of auricular reconstruction, could prevent interference with subsequent auricular surgeries and ensure stable hearing outcomes. Methods We retrospectively examined four patients with unilateral microtia who underwent VSB implantation before auricular reconstruction. The incision line was placed approximately 5 cm posterior to the posterior edge of the temporomandibular joint, ensuring that it remained at least 2 cm away from the future area of auricular reconstruction. The VSB implantation procedure involved skin incision, subperiosteal dissection, mastoidectomy, and placement of the VSB implant, with a floating mass transducer attached to the head of the stapes. More than a year later, two-stage auricular reconstruction was performed. Results All patients underwent successful auricular reconstruction after VSB implantation. During the first stage of costal cartilage grafting, subcutaneous pockets were created without encountering congestion or compromised skin flaps, and the grafted cartilage maintained a good contour. In the second stage of auricular elevation, the mastoid fascial flap was elevated with adequate blood flow, and careful dissection prevented exposure or damage to the VSB device. Postoperatively, the reconstructed auricles exhibited stable contour. Audiometric evaluation revealed no deterioration in hearing outcomes, indicating that the VSB device worked well. Conclusion This method allows safe and effective VSB implantation prior to auricular reconstruction, without hindering subsequent procedures. By maintaining an appropriate distance between the incision line and planned area of reconstruction, early hearing rehabilitation and successful auricular reconstruction can be achieved. This approach may serve as a practical standard for treating patients with microtia atresia who require early hearing intervention.